Relationship Between Antenatal Care History and Parenting Patterns with the Incidence of Stunting in Toddlers - Harumi, Ani Media; Wardani, Novita Eka Kusuma; Sholikah, Siti Mar’atus (Journal La Medihealtico, 2025)
This study aims to analyze the relationship between antenatal care history and parenting patterns in toddlers with the incidence of stunting in the Wonoayu Health Center area, Sidoarjo. Through a quantitative research design with a cross-sectional approach, data were collected from 120 mothers who have toddlers, using questionnaires and observation sheets. The results of the analysis showed a significant relationship between antenatal care history and parenting patterns with the incidence of stunting. Statistical tests with logistic regression showed that improvements in antenatal care and parenting patterns can reduce the risk of stunting in toddlers. This study provides important insights into the importance of early intervention and education for mothers to improve child health and prevent stunting in the community. Thus, recommendations to strengthen maternal and child health programs, as well as increase public awareness of good parenting patterns, are needed to support optimal growth and development of toddlers.